The HURRIER process for experimentation in business‐to‐business mission‐critical systems. Issue 5 (5th October 2021) - Issa Mattos, David; Dakkak, Anas; Bosch, Jan; Olsson, Helena Holmström
Abstract: Continuous experimentation (CE) refers to a set of practices used by software companies to rapidly assess the usage, value, and performance of deployed software using data collected from customers and systems in the field using an experimental methodology. However, despite its increasing popularity in developing web‐facing applications, CE has not been studied in the development process of business‐to‐business (B2B) mission‐critical systems. By observing the CE practices of different teams, with a case study methodology inside Ericsson, we were able to identify the different practices and techniques used in B2B mission‐critical systems and a description and classification of the four possible types of experiments. We present and analyze each of the four types of experiments with examples in the context of the mission‐critical long‐term evolution (4G) product. These examples show the general experimentation process followed by the teams and the use of the different CE practices and techniques. Based on these examples and the empirical data, we derived the HURRIER process to deliver high‐quality solutions that the customers value. Finally, we discuss the challenges, opportunities, and lessons learned from applying CE and the HURRIER process in B2B mission‐critical systems. Abstract : The HURRIER process combines existing validation techniques together with experimentation practices to deliver high‐quality software that customers value.